Chromium – An essential mineral - Lindemann, Merlin D.; Cho, Jin H; Wang, M Q (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary The status of chromium (Cr) is not a new question. Cr is clearly an essential nutrient; this is a position that has been held for over three decades by individual scientists, groups of scientists, and governmental committees. The most uniform response across species with regard to Cr deficiency symptoms that are responsive to Cr supplementation are alterations in glucose metabolism with special reference to peripheral tissue sensitivity to insulin. Because the body's ability to control blood glucose is critical to many life functions, and loss of ability to adequately control blood glucose can lead to many health debilitations, a consequence of Cr supplementation can be improved health and reproductive outcomes as well as improved survival rate or life span.